Collaborative Governance at the Ministry of Finance Case study: Joint Analysis for State Revenue Optimization - Dwi Maulid Diana; Yulianti Yulianti (Postgraduate Program Merdeka University, 2024)
This study aims to evaluate the implementation of The Integrative Framework for Collaborative Governance in the collaboration process in Joint Analysis at the national level of the Ministry of Finance in an effort to optimize state re-venue. In addition, this study will also examine the challenges found in the collaboration process. Using a qualitative approach, data were collected through document analysis and interviews. Resource Conditions and Policy and Legal Frameworks became contextual factors that influenced collaboration. In addi-tion, Perceived Uncertainty, Mutual Dependence, Consequential Incentives, and Initiating Leadership emerged as drivers of the Collaborative Governance Regime, especially at the Headquarters level, although with a lack of incentives observed in regional offices. While the Collaborative Dynamics showed effec-tiveness at the Headquarters, challenges hampered the implementation of Joint Analysis in regional units. These findings explain the complexity of collabo-rative governance in revenue optimization efforts and underscore the need for tailored strategies to overcome regional barriers.DOI: https://doi.org/10.26905/afr.v7i2.12986